1983
DOI: 10.1210/jcem-56-6-1209
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Binding Capacity and 5α-Reductase Activity in Pubic Skin Fibroblasts from Hirsute Patients*

Abstract: We have measured the total (cytosolic plus nuclear) androgen binding capacity of pubic skin fibroblasts from nine patients with hirsutism of various origin. Confluent intact cell monolayers were incubated with increasing concentrations (0.05-2 nM) of [3H]dihydrotestosterone ([3H]DHT) with or without a 200-fold excess of unlabeled DHT. The androgen binding capacities (mean +/- SD) were similar in normal men (411 +/- 171 fmol/mg DNA), women (310 +/- 103 fmol/mg DNA), and hirsute patients (313 +/- 141 fmol/mg DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…The predominant being 5α-R type 1 (SDR5A1) is found majorly in skin [28] . A rise in 5a-reductase activity was seen in genital and pubic skin fibroblasts from hirsute patients compared to the skin of normal women [29,30] .…”
Section: Table 6: Multivariate Logistic Regression Analysis On Associmentioning
confidence: 87%
“…The predominant being 5α-R type 1 (SDR5A1) is found majorly in skin [28] . A rise in 5a-reductase activity was seen in genital and pubic skin fibroblasts from hirsute patients compared to the skin of normal women [29,30] .…”
Section: Table 6: Multivariate Logistic Regression Analysis On Associmentioning
confidence: 87%
“…The amino acid residue 866 lies within the AR steroid-binding domain [8] and the Ins866 in patient 9 makes the formation of a functional AR-steroid complex impossible. In patients 4, 5 and 8, who were older and were unavailable at the time DNA analysis, an AR-binding assay was performed, confirming complete androgen resistance [9]. Non-parametrical tests were used for statistical analysis: the Wilcoxon signed rank sum test for the comparison of the age at peak height velocity of CAIS patients versus that of normal French boys and girls, and the Wilcoxon matched paired signed rank sum test for the comparison of the adult heights of CAIS patients versus their male and female target heights (p < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, an increased androgen binding capacity was observed in scalp hair cells of balding men (7). However, no consistent difference has been found thus far in the number or function of the androgen receptor in hirsute patients compared to normal subjects (8,9).…”
Section: Introductionmentioning
confidence: 96%
“…The 5α-reductase isoenzyme predominant in the skin is type 1 (SDR5A1) (15), which has 60% homology with 5α-reductase type 2 (SDR5A2) that is characteristic of the prostate gland (14). An increase in 5α-reductase activity was demonstrated in genital and pubic skin fibroblasts from hirsute patients in comparison to the skin of normal women (8,16). These studies have reported an increase in 5α-reductase activity even in IH, which is characterized by the absence of elevated plasma androgen levels (17).…”
Section: Introductionmentioning
confidence: 97%